2006
DOI: 10.1086/498906
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gown-Use Requirement on Hand Hygiene Compliance

Abstract: The hypothesis that a gown-use requirement might improve hand hygiene compliance in the intensive care unit could not be confirmed. In the subgroup of patients on contact precautions, improvement in hand hygiene compliance associated with the gown-use requirement was small and did not affect precare rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 31 publications
0
23
1
9
Order By: Relevance
“…27 However, the evidence that gowns prevent transmission of MRSA or VRE or that contact precautions increase the practice of hand hygiene or the use of gloves is mixed. [27][28][29][30][31][32] We observed that providers used gloves only marginally more often when they cared for patients assigned to contact precautions than when they cared for patients assigned to universal gloving (Fig. 2), and we found no evidence of an inverse relationship between the percentage of ICU patient-days that colonized or infected patients were assigned to contact precautions and the primary outcome.…”
Section: Discussionmentioning
confidence: 66%
“…27 However, the evidence that gowns prevent transmission of MRSA or VRE or that contact precautions increase the practice of hand hygiene or the use of gloves is mixed. [27][28][29][30][31][32] We observed that providers used gloves only marginally more often when they cared for patients assigned to contact precautions than when they cared for patients assigned to universal gloving (Fig. 2), and we found no evidence of an inverse relationship between the percentage of ICU patient-days that colonized or infected patients were assigned to contact precautions and the primary outcome.…”
Section: Discussionmentioning
confidence: 66%
“…Another study (18) that evaluated 1619 HW opportunies before and a er procedures in two ICUs found inferior results (5%). Adherence to HW in an ICU, determined through DO of HW dura on, methods, technique and use of gloves, found only 12.9% adherence (19) .…”
Section: Discussionmentioning
confidence: 97%
“…Com isso, outra desvantagem da observação direta seria o dispendioso trabalho dado em razão das divergências, a quantidade de tempo necessária, além dos elevados custos (38) . Vale ressaltar que, quanto menor o número de observadores, menores seriam as divergências no preenchimento dos questionários, favorecendo a análise dos dados (9)(10)(11) . Dessa forma, a falta de padronização e as falhas no registro do treinamento dos responsáveis pela coleta de dados levam a uma menor confiabilidade dos resultados obtidos, com destaque para medição de diferenças realizadas entre dois observadores.…”
Section: Observação Direta Das Oportunidades De Higienização Das Mãosunclassified
“…Estudos realizados com base nesta técnica encontraram taxas de adesão entre 7,6% -91,3% (2)(3)(4)(7)(8)(9)14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) . Vale lembrar ainda que mesmo se tratando de estudos observacionais os critérios utilizados em cada estudo variaram consideravelmente, sendo que, em alguns trabalhos, foram observadas as lavagens das mãos apenas antes do contato com o paciente; enquanto outros estudos foram além, observando a adesão durante a assistência inclusive de um mesmo paciente, diferenciando atenção nas áreas mais contaminadas para áreas menos contaminadas do corpo.…”
Section: Observação Direta Das Oportunidades De Higienização Das Mãosunclassified
See 1 more Smart Citation